Anti-disturbance fault-tolerant formation containment control for multiple autonomous underwater vehicles with actuator faults. (15th December 2022) - Xu, Jian; Cui, Yunfei; Xing, Wen; Huang, Fei; Yan, Zheping; Wu, Di; Chen, Tao
Abstract: This paper investigates the time-varying formation containment problem for multiple autonomous underwater vehicles (MAUVs) system subject to actuator faults in three-dimensional space. The leader AUVs are required to track the virtual leader AUV with time-varying offset vectors, and at the same time the follower AUVs are demanded to converge into the convex hull formed by the leader AUVs. The extended state observers (ESOs) are designed to estimate the external disturbances and unknown nonlinearities of MAUVs system in real time, hence ensuring the anti-disturbance ability of MAUVs system. The tracking differentiators (TDs) are developed so as to avoid the differential explosion issues caused by the derivatives of the virtual control laws. The distributed formation containment control laws are put forward for compensating the impacts of unknown bounded actuator bias fault and loss of actuator effectiveness fault based on adaptive control strategy. Furthermore, the stability of MAUVs system is demonstrated by means of Lyapunov stability theory. At last, a numerical simulation is presented to confirm the effectiveness of the proposed method. Highlights: A two-layer distributed formation containment control scheme is proposed, which can both guarantee the leader AUVs to track the virtual leader AUV and force all follower AUVs to asymptotically converge into the convex hull spanned by the leader AUVs. The designed adaptive control laws effectively compensate the influences of bias fault and loss-of-effectiveness fault on multiple AUVs system, where the bounds of bias fault and loss-of-effectiveness fault are unknown. The extended state observers are given for estimating the unknown nonlinearities and external disturbances in real time, which further improves the anti-disturbance capability of the system. The tracking differentiators are designed for the sake of avoiding the problem of differential explosion induced by the derivatives of the virtual control laws.